2017
DOI: 10.1371/journal.pntd.0005576
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin treatment of Loa loa hyper-microfilaraemic baboons (Papio anubis): Assessment of microfilarial load reduction, haematological and biochemical parameters and histopathological changes following treatment

Abstract: BackgroundIndividuals with high intensity of Loa loa are at risk of developing serious adverse events (SAEs) post treatment with ivermectin. These SAEs have remained unclear and a programmatic impediment to the advancement of community directed treatment with ivermectin. The pathogenesis of these SAEs following ivermectin has never been investigated experimentally. The Loa/baboon (Papio anubis) model can be used to investigate the pathogenesis of Loa-associated encephalopathy following ivermectin treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
1
27
2
Order By: Relevance
“…Microfilaraemic loads were determined microscopically on thick films. Calibrated thick blood smears were prepared by spreading a 50 μl venous blood sample from a 75 μl non-heparinised capillary tube, onto a clean slide over an area of 1.5 × 2.5 cm [ 16 ]. After drying, films were dehemoglobinized and stained with Giemsa.…”
Section: Methodsmentioning
confidence: 99%
“…Microfilaraemic loads were determined microscopically on thick films. Calibrated thick blood smears were prepared by spreading a 50 μl venous blood sample from a 75 μl non-heparinised capillary tube, onto a clean slide over an area of 1.5 × 2.5 cm [ 16 ]. After drying, films were dehemoglobinized and stained with Giemsa.…”
Section: Methodsmentioning
confidence: 99%
“…L. loa naturally infects an endangered species of monkey, the drill ( Mandrillus leucophaeus ), endemic to Central Africa. As a surrogate non-human primate model, the life cycle of L. loa can be maintained via experimental infection of splenectomised baboons 16,17 , a model which has recently been utilised to initiate exploratory pathology studies of IVM-associated neurological SAE 18,19 . This model has also generated adult and mf parasitic stages for a range of ex vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that in the clinical and community trials it was demonstrated that a single dose of ivermectin can lead to 80–90% reduction of L . loa microfilaraemia [ 15 , 16 ], one could have expected to have a lower fraction of individuals still harbouring L . loa mf.…”
Section: Discussionmentioning
confidence: 99%
“…loa presents an intriguing vicious cycle that was illustrated recently with the development of an animal model of L . loa encephalopathy [ 15 , 43 ]. Ivermectin is highly efficacious in clearing the L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation